Effects of a multimodal rehabilitation program in COVID-19 patients admitted to the Intensive Care Unit: A quasi-experimental study - Rodríguez-Montoya, Ronald Milton (2021)
Background: Patients with severe COVID-19 evolve to acute respiratory distress syndrome (ARDS) and require management in Intensive Care Units (ICU) where they are exposed to immobilization, immunosuppression, malnutrition, nosocomial infections; may develop ICU Acquired Weakness (ICUAW), which increases with the stay and use of mechanical ventilation (MV).There is evidence of the use of different modalities in rehabilitation to mitigate these effects. Goal: To determine the efficacy of a Multimodal Rehabilitation Program (MRP) in reducing the number of days of mechanical ventilation and stay in patients hospitalized for COVID-19 in ICU, as well as to describe its clinical and hospital characteristics. Material and Methods: An quasi-experimental study was designed, with sequential sampling and without blinding. A control and intervention group was formed, with 32 participants each. A Multimodal Rehabilitation Program (MRP) based on four therapeutic modalities was applied and the intervention was quantified through the use of proposed indicators. Results: The variation in days of ICU stay and days of MV were similar in both groups. The Multimodal Rehabilitation Index (iMR) ranged from 0.1 to 2.7 (mean = 1.2, SD = 0.7) and had significance for cut-off points ≤ 0.81 and ≤ 0.94 in mortality (p = 0.02) and Ventilator-free days at 28 days (VFDs-28) (p = 0.01). Conclusions: No statistically significant difference was found in favor of the intervention in terms of days of stay in the ICU and days of MV. Explanatorily, it was reported that iMR was related to (VFDs-28) and mortality in patients with severe COVID-19.